4R Management of Phosphorus Fertilizer in the Northern Great Plains. Issue 3 (27th May 2021) - Sever, Megan
Abstract : Soil scientists Don Flaten and Cynthia Grant recently put together a comprehensive reference for phosphorus fertilizer management across the Northern Great Plains. This article summarizes their findings on managing this nutrient using the 4R approach of right rate, source, placement, and timing. Earn 1.5 CEUs in Nutrient Management by reading the article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/951 .